Profiling the diversity of morphological traits for future Malaysian breeding programme in capsicum genetic resources - Sarobo, Zulaikha (2019)
Capsicum spp. is a very important crop in Malaysia because of high demand in local market. However, local chili production is low mainly due to poor seed quality or unavailability of high yielding varieties under tropical environment. Thus, the aim of the research project was to assess the morphological characteristics in 45 Capsicum genetic resources, collected from local and exotic resources. The Capsicum genotypes were characterized for speed of germination (SG), germination energy (GE), plant height (PH), leaf area (LA), days to flowering (DFL), days to fruiting (DFR), total fruit weight (TFW), fruit length (FL), fruit dry weight (FDW) and seed dry weight (SDW). The data of these traits were subjected to analysis of variance (ANOVA), correlation analysis and multivariate analysis using cluster analysis based on percent similarity coefficient. ANOVA revealed that local as well as exotic Capsicum genetic resources exhibited diversity for all the morphological parameters. TFW showed the maximum diversity as compared to other traits. However, the least diversity was shown in PH trait. TFW exhibited positive correlation with FDW, SDW, LA, DFR, DFR and FL for both exotic and local Capsicum spp. Thus, direct selection for traits; TFW, FDW, SDW, LA, DFL, DFR, and FL will be helpful for selection of chili varieties in Malaysia. Through cluster analysis, both genotypes of exotic and local Capsicum spp. had been clustered into two major cluster at 64.08% similarity coefficient, and also grouped into 12 sub-clusters at 78.88% similarity coefficient. Cluster I to cluster VIII was in major group 1 while cluster IX to XII in major group 2. For better emphasis, PA10, PA38 and L10 were the most unique compared to the rest because they were classified as a single genotype in a node with similarity coefficient at 76.34%. Genotype L10 was the most outstanding compared to the rest due to its uniformed flowering and fruiting. Therefore, the selection of high yielding variety within both major clusters can be an advantage for future breeding programme.